Body maps: photography, science, and sensoriality (Revista Tempo e Argumento, 2016)
AbstractThis article focuses on discussing the uses of photography through two papers presented at the 1937 Congress of the Brazilian National Sung Language, by Edgar Roquette-Pinto and João Lellis Cardoso. The Congress, organized by Mário de Andrade, aimed to define and devise strategies to systematize pronunciations in the Brazilian Portuguese language. These presentations proposed using ‘phonophotography’ – or ‘sound picture’ – as a tool to decode and correct the ‘flaws’ of spoken/sung language in various regions in the country. Based on the experiences of the U.S. physicist Dayton Clarence Miller and the psychologist Carl Seashore, such papers represented, even naively, the eagerness to master instincts, which may be accessed via sound, through the visual field. Keywords: Photography; Sound; Congress Of The Brazilian National Sung Language; Sensoriality. Original title: Mapas do corpo: fotografia, ciência e sensorialidade.